Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Matematika Materi Perkalian Kelas II SD Negeri 25 Sungai Pinyuh - Muzakki; Risdiana Andika Fatmawati; Siti Nur Asmah (Jurnal Pendidikan Indonesia (JOUPI), 2024)
This study aims to describe the types of errors, calculate the number and percentage of students who make mistakes in solving mathematical problems on multiplication material. This study uses a qualitative approach and is descriptive in type, while data collection is observation, interviews, and documentation. The subjects of this thesis are grade II Elementary School students. This study found that there were five errors made by students on multiplication material, namely, errors in reading questions, errors in understanding problems, errors in transforming problems, errors in process skills and errors in writing answers.